Sports and Recreational Activities following Total Ankle Replacement - Usuelli, Federico Giuseppe; Pantalone, Andrea; Maccario, Camilla; Guelfi, Matteo; Salini, Vincenzo (Joints, 2017)
Purpose In literature, there is a controversy regarding whether patients who have undergone total ankle replacement (TAR) can participate in sports and recreational activities. The purpose of this study was to report change in sports activity level after TAR.Methods A retrospective study was performed, enrolling 76 patients with symptomatic end-stage ankle arthritis who underwent TAR from May 2011 to October 2014. Patients were mainly males (44/76; 58%) and 56 years old on average (range: 22.3–79.6 years) at the time of surgery. They were treated with mobile-bearing prosthesis implanted with an anterior approach. Patients were evaluated preoperatively and 12 months postoperatively. Pain and function were assessed using the American Orthopaedic Foot and Ankle Society (AOFAS) ankle and hindfoot score, the visual analog scale (VAS) pain score, and the 12-Item Short Form Health Survey (SF-12) – physical component summary (PCS) and mental component summary (MCS). Activity level was assessed with the University of California at Los Angeles (UCLA) activity scale.Results At 12 months postoperatively, statistically significant increase was reported for AOFAS scores (from 32.8 ± 12.7 preoperatively to 72.6 ± 13.3; p < 0.001), SF-12 PCS (from 34.3 ± 5.1 preoperatively to 45.4 ± 6.4; p < 0.001), and SF-12 MCS (from 39.8 ± 7.5 preoperatively to 51.4 ± 6.1; p < 0.001). A statistically significant decrease was detected in VAS pain score (from 8.7 ± 1.6 preoperatively to 2.2 ± 1.6; p < 0.001). The UCLA activity levels increased significantly from 2.4 ± 0.8 to 6.3 ± 2.3 (p < 0.001).Conclusion Pain and function significantly improved in patients affected by ankle osteoarthritis, who underwent TAR, at 1-year follow-up. In addition, activity level showed a significant increase respect to preoperative condition.Level of Evidence Level IV, retrospective case series.
Keywords: ankle; arthroplasty; osteoarthritis; replacement; sport